Notes on some tardigrades from southern Mexico with description of three new species - Pilato, Giovanni; Lisi, Oscar (Zootaxa, 2006)
Eight species of tardigrades are reported from southern Mexico (Chiapas: Selva El Ocote). Two of them (Pseudechiniscus juanitae De Barros, 1939 and Doryphoribius gibber Beasley & Pilato, 1987) are new to Central America, three are new to science: Pseudechiniscus gullii sp. n., Macrobiotus contii sp. n. and Minibiotus continuus sp. n.